A comparative study between CT angiography and flow parameters in hemodynamic phantom of carotid stenosis evaluated by duplex sonography - Seidlová, Anna; Svoboda, Norbert; Voldřich, Richard; Kešnerová, Petra; Matějka, Roman; Pakizer, David; Školoudík, David; Netuka, David (3D printing in medicine, 2025)
BACKGROUND: The use of 3D-printed hemodynamic phantom of a stenotic carotid artery has not been extensively investigated. Our study aims to address this gap by exploring the correlation between CTA and flow parameters in hemodynamic phantom. METHODS: Patients with carotid stenosis were included in a prospective study. A realistic phantoms of carotid artery stenoses were 3D-printed based on CT angiography. Stenosis severity and hemodynamic flow parameters in the phantom evaluated using duplex sonography were correlated with CTA. The primary outcome was to compare the evaluation of the percentage of stenosis based on the measurement of diameter reduction and area reduction of the carotid artery among CTA, a 3D model constructed from CTA data, and ultrasound measurement of stenosis percentage within the 3D printed phantom. The secondary outcome was to determine whether the percentage of stenosis measured by ultrasound in B-mode or ultrasound-measured flow velocities (PSV, EDV) better correlates with the stenosis percentage derived from CTA and the phantom. RESULTS: The study included 95 subjects (average age 71 years, 75% male) with carotid stenosis, 39% were symptomatic. Significant correlations were found between ultrasound B-Mode findings on the phantom and CTA, with the strongest correlations for area reduction (Spearman r = 0.615, p < 0.0001) and diameter reduction (Spearman r = 0.465, p < 0.0001). The most robust correlation between PSV and EDV in stenosis and the percentage of stenosis was identified between PSV in stenosis and the percentage of stenosis by diameter reduction, as evaluated through ultrasound. The Spearman correlation coefficient revealed a relatively strong correlation, with a value of r = 0.444 (p < 0.0001), and the Kendall Tau correlation coefficient also demonstrated significance, with a value of r = 0.302 (p < 0.0001). CONCLUSIONS: A significant correlation between CTA and duplex sonography measurements on the carotid phantom was demostrated, suggesting the potential utilization of the phantom in testing hemodynamic parameters of carotid stenosis.